To what extent are African Countries Vulnerable to climate change? Lessons from a new indicator of Physical Vulnerability to Climate Change - Patrick Guillaumont; Catherine Simonet (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
This paper examines the vulnerability of African countries to climate change, for which they are not responsible. It is based on an index of structural or physical vulnerability to climate change at the country level, denominated below by the acronym PVCCI. This index has been created recently by the authors, and has been made available on the FERDI website. The design of this index draws both on the environmental literature, and some principles used by the United Nations to measure structural economic vulnerability via the Economic Vulnerability Index (EVI) for the identification of the Least Developed Countries (LDCs). As an environmental index, the PVCCI uses components which reflect only the physical consequences of climate change which can directly affect population welfare and activity, rather than on an assessment of their economic consequences. At the same time this index of vulnerability to climate change refers only to a vulnerability which does not depend on the present will of African countries. In other words, this index refers to a "structural" or "physical" vulnerability, putting to one side resilience which is usually integrated into vulnerability assessments, but is largely dependent on policy factors. The components of this new index respectively capture two kinds of risks related to climate change: the increasing risk of recurrent shocks (such as droughts), and the risks of progressive irreversible shocks (such as flooding due to higher sea level). Moreover the components refer both to the likely size of the shocks and to the country exposure to these shocks.
Keywords: E01; E61; C43; O10; O13; O19; Q54; Q56; 330